Comparison of objective and subjective operator fatigue assessment methods in offshore shiftwork. (July 2017) - Mehta, Ranjana K.; Peres, S. Camille; Kannan, Pranav; Rhee, Joohyun; Shortz, Ashley E.; Sam Mannan, M.
Abstract: The oil and gas extraction (OGE) industry continues to experience an elevated fatality rate; OGE workers are exposed to intensive shift patterns and long work durations inherent in the OGE environment, which can lead to fatigue, thereby increasing risks of incidents and injuries. As such, fatigue assessment methods play a critical role in identifying and subsequently managing fatigue in offshore operators. The aims of this observational study were to explore the effect of offshore shiftwork on physiological and subjective fatigue outcomes. Ten male operators (age: 31.3 (6.1) years; stature: 1.72 (0.1) m; weight: 85.24 (9.8) kg) were monitored throughout their daily shifts for six days on an offshore drillship using intrinsically safer physiological sensors that recorded various physiological parameters. Additionally, existing subjective fatigue scales from the literature were employed to obtain perceptions of fatigue. Six of the ten operators underwent swing shift in the middle of the data collection period. Physiological results indicate that overall average heart rate (an indicator of fatigue) were elevated for all operators and remained elevated for those who started and ended their work on the day shift. Operators' subjective reports of fatigue were relatively high for acute fatigue and intershift recovery as well as for lack of effort and sleepiness; however, the physiological measures were not consistently correlated with the subjective measures of fatigue. The study outcomes identified a critical gap in fatigue assessment in OGE operations; existing fatigue surveys for the general (or other) working populations are not comprehensive of OGE operations and are thus not applicable for OGE workers, nor are they validated against physiological fatigue outcomes in OGE workers. Highlights: Fatigue assessment in offshore shiftwork is poorly addressed. Offshore shiftwork was assessed using physiological and subjective fatigue outcomes. Physiological and subjective fatigue outcomes did not correlate consistently. Existing physiological assessment of fatigue is not practical in offshore environments. Existing subjective fatigue methods are not effective in capturing offshore shiftwork fatigue.